ANALISIS EFEKTIVITAS PEMASARAN DIGITAL DALAM MENINGKATKAN BRAND AWARENESS PADA UMKM DI KABUPATEN GOWA - Ambo Uleng (Liquidity Jurnal Ilmu Manajemen dan Bisnis, 2026)
The development of digital technology has transformed marketing patterns from conventional approaches to online platforms that are more interactive, measurable, and adaptive. Micro, Small, and Medium Enterprises (MSMEs), as the backbone of the regional economy, are required to adapt to digital transformation to maintain competitiveness. Gowa Regency, as a region with significant MSME growth, faces challenges in optimizing digital marketing strategies, particularly in building brand awareness. This study aims to analyze the effectiveness of digital marketing in increasing MSME brand awareness in Gowa Regency and identify the most dominant variables influencing it. The study used a quantitative approach with an explanatory survey design of 120 MSMEs actively utilizing digital media in marketing activities. Data analysis was conducted using multiple linear regression. The results showed that digital marketing simultaneously had a significant effect on brand awareness with a significance value of 0.000 and a coefficient of determination (R²) of 0.68. Partially, customer interaction (engagement) and content quality variables had the most dominant influence. These findings indicate that the success of digital marketing depends not only on the frequency of promotions, but also on the quality of communication and relationships built with consumers. This research provides empirical contributions to the development of digital strategies for MSMEs at the regional level as well as policy recommendations for strengthening digital literacy and capacity of business actors.